Water Relations of Evergreen Sclerophylls. I. Seasonal Changes in the Water Relations of Eleven Species from the Same Environment (Annals of Botany, 1990)
Leaf water relationships were studied in eleven evergreen sclerophyll species from a macchia near Athens, Greece. Water (ψ), solute (ψs) and turgor (ψp) potentials as well as relative water content (RWC) and stomatal conductance were measured during the course of a year. Relatively high values of water potential were measured initially in the young expanding leaves during the 60–90 d of the growth period. After this period a soil moisture deficit developed and leaves increased to full size. During the drought period leaf water potential and solute potential values, as well as stomatal conductance were low. The results show that during the dry season (Jun.–Aug.) all species are at or near zero turgor and this occurs in Arbutus, Myrtus and Nerium at around −1.5 MPa, in Ceratonia, Pistacia and Quercus at around −2.0 MPa, in Laurus, Olea and Phillyrea below −3·5 MPa. These values largely reflect differences in ψs at this time. Also, the seasonal variations in the water relations components reflect the responses of the different species to variation in water availability.